Legal Policy On Imposing Sanctions On Corruption Crimes In Indonesia - Purnama, Chandra (Inspiring Law Journal, 2024)
Corruption is currently one of the many major challenges that must be faced by the Indonesian nation. To some extent, corruption not only threatens the environment, human rights, democratic institutions and basic rights and freedoms, but also hinders development and exacerbates poverty. Based on the results of the study, it is known that; The legal regulation of corruption in Indonesia is regulated in Law No. 31 of 1999 as amended by Law No. 20 of 2001. In addition to imprisonment and fines, this law also regulates additional sanctions such as revocation of political rights and confiscation of assets. Additional sanctions aim to provide a deterrent effect, but their implementation is still hampered by inconsistent law enforcement and the difficulty of returning assets. The policy of sanctions for corruption crimes in Indonesia aims to provide a deterrent effect through principal and additional penalties, such as revocation of political rights and confiscation of assets